Reliability engineering : theory and practice - Birolini, Alessandro, 1940- (Springer, 2017)
This book shows how to build in, evaluate, and demonstrate reliability and availability of components, equipment, systems. It features checklists for design reviews and more than 100 practice oriented examples.
Keywords: Reliability (Engineering); elektronické knihy; electronic books